[BP.04.03] SHORT-TERM AND LONG TERM RELATIONSHIP BETWEEN HEART RATE AND AUGMENTATION INDEX IN YOUNG TO MIDDLE AGE SUBJECTS. (September 2017) - Saladini, F.; Fania, C.; Mos, L.; Mazzer, A.; Garbelotto, R.; Ovan, D.; Longo, D.; Perkovic, D.; Vriz, O.; Palatini, P.
Abstract : Objective: Several studies have shown that the augmentation index (AIx), the primary outcome derived from pulse wave analysis, is negatively correlated with heart rate (HR). This led some authors to claim that the use of HR-lowering drugs may be detrimental in hypertension. The aim of this study was to assess the acute and chronic relationships of HR with AIx in a sample of normotensive and hypertensive adults younger than 45 years. Design and method: We studied 347 subjects (259 men) from the HARVEST study (mean age 37.3 ± 10.1 years). Central blood pressure and AIx were evaluated with Specaway DAT system and small artery compliance (SAC) with HDI Pulse Wave device. HR was measured at baseline in the office (mean of 6 readings) and with 24 h ambulatory recording. The arterial elasticity assessment was performed after a mean of 6.7 years from baseline. In multivariate regression analyses, AIx and central systolic BP were used as dependent variables and office HR or night-time HR as predictors adjusting for age, sex, BMI, height, mean BP, smoking, alcohol, physical activity habits, SAC, and pulse wave velocity. Results: Adjusted office HR measured at the time of arterial elasticity assessment was inversely correlated with AIx (p = 0.001) a relationship which was attenuated after physical activity (p = 0.004) and ejection duration (p = 0.015) were taken into account. In addition, office HR was inversely correlated with central BP (p = 0.039) a relationship which was no longer significant after physical activity (p = 0.14) or ejection duration (p = 0.58) were accounted for. In contrast, in fully adjusted models baseline average night-time HR was a significant positive predictor of AIx (p < 0.001) and central BP (p = 0.014) measured 6.7 years later. Adjusted AIx was 20.0 ± 3.0% in the top night-time HR quintile, 14.9 ± 1.4% in the 3 intermediate quintiles, and 6.5 ± 2.8% in the bottom quintile. Baseline office HR was unrelated to both AIx and central BP. Conclusions: These data confirm that HR is negatively related to AIx when measured at the time of arterial elasticity assessment. However, HR measured with ambulatory monitoring is an independent positive long-term predictor of AIx and central BP.